The Toxic Impact of Monosodium Glutamate in Rats - Krynytska, Inna; Marushchak, Мariya; Naumova, Lyudmyla; Mazur, Lyudmyla (Jordan Medical Journal, 2019)
Background. Nowadays, more than 2500 additives are intentionally added to food in order to keep certain properties or to extend shelf life. One of the most common food additives in Ukraine and in Europe is monosodium glutamate. Potentially negative health effects of monosodium glutamate prompt us to question safety of its wide-spread use.Objectives. In this study we defined the effect of monosodium glutamate (E 621) on the main markers of endogenous intoxication in rats.Materials and Methods. Experimental studies were conducted on 72 nonlinear male white rats weighing 150-180 g. The experimental animals were administered monosodium glutamate at a dose of 30 mg/kg body weight (corresponds dose 2 g per day in humans) for 7, 14 and 30 days. The control group of animals was given normal saline. Syndrome of endogenous intoxication was evaluated using measurements of low, medium, and high molecular weight substances in blood plasma, red blood cell suspension, and urine.Results. Our results indicated a shift of the markers of intoxication syndrome towards mainly catabolic substances. The results obtained after one week of the experiment correspond with phase of partial compensation, characterized by increased concentrations of low and middle molecular weight substances in red blood cells and plasma. After two weeks and up to one month of the experiment, the predominantly catabolic markers of endogenous intoxication continue to increase in erythrocytes and plasma, indicating a shift to the phase of partial decompensation to systems and organs of detoxification.Conclusion. The administration of monosodium glutamate at a dose of 30 mg/kg body weight was associated with development of excessive contents of low and middle molecular weight substances with reduced ability of kidneys to excrete toxic products.